Strengthening tuberculosis diagnosis in a low-resource setting: experience learned in Dodoma, Tanzania - Cannas, Angela; Paglia, Maria Grazia; Sakhoo, Dominick Calistus; Vairo, Francesco; Doulla, Basra; Nguhuni, Boniface; Chaula, Zainab; Mlumba, Raphael; Mirrione, Maurizio; Bevilacqua, Nazario; Nicastri, Emanuele; De Nardo, Pasquale; et al. (The Journal of Infection in Developing Countries, 2013)
Introduction: Diagnosing tuberculosis in low-resource settings mostly relies on sputum smear microscopy. Improvement through capacity building is a priority. This project aimed to strengthen tuberculosis diagnosis at an intermediate level laboratory. Methodology: The Italian National Institute for Infectious Diseases and the Italian Development Cooperation closely collaborated with regional and national institutions and reference laboratories to provide laboratory setup, equipment and reagents, personnel training, and the implementation of culture and quality assessment programs at Dodoma Regional Hospital, Dodoma, Tanzania. Results: Microscopy sensitivity was increased, personnel were trained, and culture techniques and quality assessment programs were introduced. Conclusions: Implementing tuberculosis diagnosis in resource-constrained settings is feasible and represents a basis for further strengthening.